ANALISA HASIL INSTALASI PENGELOLAAN AIR LIMBAH RUMAH SAKIT - M Yasir Pohan; Elita Amrina (Jurnal Bionatural, 2025)
Hospital is one of the health facilities as an effort to maintain and improve public health. The purpose of this study was to evaluate the liquid waste management system at the Hospital. Descriptive research method with a qualitative approach. Data collection was carried out by interviews, document reviews and direct field observations. The variables studied were the process of managing liquid waste originating from the hospital. Research Results Based on the results of interviews and observations, the management of liquid waste at the Hospital has an Aerobic method mixed with Enzyme Chemicals. The sources of wastewater that flow into the Wastewater Treatment Plant come from all activities of the Hospital. showing the results of outlet tests with parameters of Temperature, pH, BOD, COD, TSS, oil and fat can be said to be optimal in the process of processing liquid waste because the results of the Analysis have met the standard quality standards. The conclusion of the characteristics of hospital liquid waste by testing the outlet has met the standard quality standards.